Meaning Relations in Indonesian Semantic Studies - Simorangkir, Agustina Verawati; Tarigan, Novia Sari; Banjarnahor, Pretty Grace; Sari, Yuliana (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This research examines the relationship between meaning in Indonesian. Developments in the field of science and advances in technology can cause changes in the meaning of a word. This is where a word slowly experiences degradation caused by a new view. The meaning of a sentence cannot be separated from the role of language in it. Language functions as a medium of communication. Meaning as an element of language is an element that has the potential to change because meaning is related to concepts and human thoughts that do not stop. This means that language contains meaning that can be understood. Therefore, in studying languages, especially Indonesian, there are many branches of scientific disciplines, one of which is the science that studies meaning which is called semantics. In the context of the linguistic hierarchy, the meanings of words that are related to each other are called meaning relations. Meaning relationships can take various forms. In every language, including Indonesian, we often find meaning relationships or semantic relationships between words or other language units. Relationships or relationships related to meaning have many variations, so the focus of meaning studies includes similarity of meaning (synonymy), opposite meaning (antonymy), double meaning (polysemy), inclusion of meaning (hyponymy) and multilevel meaning (homonymy).